The rediscovery of India : a new subcontinent - Khan, Ansar Hussain, 1928- (Hyderabad : Orient Longman, 1995)
History of India from the earliest times to the present day.
Includes bibliographical references (p. [333]-341) and index.
Keywords: India -- History